DIGITAL-BASED MANAGEMENT OF NEW STUDENT ADMISSIONS IN MADRASAH ALIYAH - Frans Angger Bagus Sancoko (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The management of new student admissions is an important component in improving the quality of educational institutions, including Madrasah Aliyah. In the digital era, the implementation of digital-based admission systems has become a strategic solution to increase efficiency, transparency, and accessibility in the admission process. This study aims to analyze the management of digital-based new student admissions in Madrasah Aliyah and to identify its benefits and challenges in educational management. This research uses a qualitative approach through library research methods. Data collection techniques were conducted using documentation from books, scientific journals, and other relevant academic sources. Data analysis was carried out using content analysis to interpret and synthesize information related to digital-based admission management. The results show that the implementation of digital-based admission systems in Madrasah Aliyah can improve administrative efficiency, provide wider access for prospective students, and create transparency in the selection process. However, several challenges remain, including technological infrastructure limitations, digital literacy among education stakeholders, and the need for continuous system development.